Comparative Study: Education Policy in Indonesia Versus Japan in Realizing Sustainable Development Goals 4 (Quality Education) - Siami, Ayuni Nur (The Easta Journal Law and Human Rights, 2025)
This study compares the education systems and quality in Indonesia and Japan in an effort to achieve Sustainable Development Goals (SDGs) goal number 4, namely quality education. This study aims to identify the strengths and weaknesses of each education system, examine the education policies implemented, and examine the role of culture and society in supporting the achievement of quality education. With a descriptive-qualitative approach based on literature studies, this study found that Japan has succeeded in achieving most of the SDGs targets for quality education through consistent education policies, human resource development, and utilization of technology. In contrast, Indonesia still faces various challenges, ranging from regional disparities, teacher quality, to limited education infrastructure. The results of this analysis are expected to provide input for policy makers in Indonesia in improving the quality of national education.